TEA LEAVES GMB SERIES CLASIFFICATION USING CONVOLUTIONAL NEURAL NETWORK - Syamsul Rizal; Nor Kumalasari Caecar Pratiwi; Nur Ibrahim; Hurianti Vidya; Sofia Saidah; R Yunendah Nur Fu'adah (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2020)
This study classifies GMB series tea leaves by using a convolutional neural network as a classification system. GMB series tea are the superior tea seeds in Indonesia. Gambung series, namely: GMB 1 to GMB 11, are planting material seeds that have been recommended by the Ministry of Agriculture. The potential of these tea series yield of 4,000 - 5,800 kg / ha of dried tea. The morphological similarity level of GMB 1 to GMB 11 is very high, because many elders from the clones are from the same crossing parents. During this time, the process of identifying GMB clones 1 through GMB 11 is done manually using the visual eye of an experts at PPTK Gambung. These experts are limited to be able to identify each tea series. This process is susceptible to errors in the reading of clone types, and is very dependent on the presence of the experts. If an error occurs in the process of identifying the type of clone, it will interfere with the nursery process. Errors in the selection of recommended clones will harm the process of a long period of time, because the economic age of tea plants can reach until 50 years. The potential loss of production due to misuse of plant material can reach 1,200 kg / ha per year. Against the background of these problems, it is very necessary to have a system to identify the GMB series clone. Continuous studies has been conducted to build an automation system for the identification and classification of GMB series tea clones. The system is designed using the Convolutional Neural Network (CNN) method. The results obtained from this system output in the form of accuracy with a value of 85%.